Matrine Protects Against MCD-Induced Development of NASH via Upregulating HSP72 and Downregulating mTOR in a Manner Distinctive From Metformin - Mahzari, Ali; Li, Songpei; Zhou, Xiu; Li, Dongli; Fouda, Sherouk; Alhomrani, Majid; Alzahrani, Wala; Robinson, Stephen R.; Ye, Ji-Ming (Frontiers in Pharmacology, 2019)
The present study investigated the effects of matrine on non-alcoholic steatohepatitis (NASH) in mice induced by a methionine choline-deficient (MCD) diet and the mechanism involved. The study was performed in C57B/6J mice fed a MCD diet for 6 weeks to induce NASH with or without the treatment of matrine (100 mg/kg/day in diet). Metformin was used (250 mg/kg/day in diet) as a comparator for mechanistic investigation. Administration of matrine significantly reduced MCD-induced elevations in plasma ALT and AST but without changing body or liver fat content. Along with alleviating liver injury, matrine suppressed MCD-induced hepatic inflammation (indicated by TNFα, CD68, MCP-1, and NLRP3) and fibrosis (indicated by collagen 1, TGFβ, Smad3, and sirius-red staining). In comparison, metformin treatment did not show any clear sign of effects on these parameters indicative of NASH. Further examination of the liver showed that matrine treatment rescued the suppressed HSP72 (a chaperon protein against cytotoxicity) and blocked the induction of mTOR (a key protein in a stress pathway). In keeping with the lack of the improvement of the NASH features, metformin did not show any significant effect against MCD-induced changes in HSP72 and mTOR. Matrine protects against MCD-induced development of NASH which is refractory to metformin treatment. Its anti-NASH effects involve enhancing HSP72 and downregulating mTOR but do not rely on amelioration of hepatosteatosis.